The Impact of M&As on the Operating Performance and Shareholder Wealth: Evidence from UK Market - Yue, Jing Bing (2012)
The number of mergers and acquisitions (M&As) are growing at a rapid speed in emerging markets, and M&As have become the most important and useful corporate tool to pursue strategic growth (Seth, 1990; Anslinger and Copeland, 1996). M&A activities not only can help companies to change their course and the careers of managers, but also can create great value for shareholders (Tuch and O’Sullivan, 2007). However, according to Graham, Lemmon and Wolf (2002) more than 50 per cent of the mergers result in a reduction in the value of shares and another 25 per cent have indicated no significant increase. The analysis is based on both accounting methodology as well as an event study in relation to UK based acquiring companies. Accounting methodology is based on each company’s financial ratios to analyse whether M&A activities can create a significant positive value for acquirers or shareholders. Moreover, we based on a simple t-test to know whether M&As have significant influence on shareholder’s value. After that, we apply a further approach of an event study to evaluate the abnormal performance following a merger or an acquisition. Finally, through cross-sectional regression analysis we test the most important and popular variables affect on the firm’s cumulative abnormal returns around the announcement date.